PENGARUH PEMBERITAAN SURAT KABAR TERHADAP PERSEPSI MASYARAKAT PENGGUNA JASA TRANSPORTASI UDARA DI SURABAYA (Kasus Studi Kecelakaan Pesawat Adam Air) - Elton, Lydia (Scriptura, 2007)
Cases of aircraft accidents that have been frequently exposed in mass media both print-and-electronic media have led its news to spread expansively among societies. "Mass media have very significant effects on perceptions that can be established in minds of public in general. Media of mass communication can affect changes and have really done it, moreover if it is related to interests of a lot of people. Media are also capable of drumming up unity and public opinion on particular events". Whereas problem formulation in the research is how effects of newspaper's news reports on aircraft accidents on perception of Air-Transportation Service User-Society in Surabaya (related to news reports around accident of Adam Air plane)? Research type that was carried out was quantitative explanation. Based on the research results, thusly conclusion could be obtained as follows: there were no significant effects between variable of newspaper's news on accident case of Adam Air on perception of air-transportation service user-society in Surabaya. Hypothesis of research 1-Ia was rejected and Ho was accepted in which it did not signify that there were no effects of newspaper's news on public perception. Furthermore, the changing public perception such as in theories according to Rivers that mass media have significant effects in determining perceptions on a particular event, it is also due to long time span between accident event and time of questionnaire distribution thusly resulting in consequential probability that public perception or passenger psychology have changed.